Analysis of quantitative genetic variation using aromatic and non aromatic genotypes in rice - Krishna, L; Raju, Ch. Surender; Kumar, S. Sudheer (ORYZA-An International Journal of Rice, 2017)
The gene effects for grain yield and its component characters were studied using five generations viz., P1, P2, F1, F2, and F3 in ten crosses involving five aromatic and three non-aromatic varieties. Epistasis was noticed in majority of the characters for all the crosses. This study confirmed that, in addition to main effects (additive/dominance) the non allelic interaction effects were also predominant in expression of the desirable metric traits related to yield. The nature and magnitude of gene effects differ depending on cross and quantitative trait. Hence, specific breeding strategy has to be adopted for each cross to get immediate benefit in grain yield and improve traits in rice. Based on the magnitudes of fixable genetic variation (‘d’ & ‘i’ types) and per se, pedigree selection in segregating generations with respect to crosses, BPT 5204 x Akshyadhan, Akshyadhan x NLR 145, Akshyadhan x Pusa 1121 were recommended.